IMPLEMENTATION OF PROGRAMMED LEARNING IN THE HIGHER MILITARY EDUCATIONAL INSTITUTIONS - Melnyk, Yu. B. (Honor and Law, 2019)
The article deals with the history of formation of programmed instruction and its implementation in particular the higher military educational institutions (HMEI). Refined essence of concepts «programmed (step by step) learning». The algorithm implementation of educational programs and the organization of training cadets HMEI in accordance with the requirements of programmed learning. On the basis of programmed learning, a system of training future officers.